Real Costs and True Potential - Hanson, John (Maine Policy Review, 1993)
At the "Rethinking State Government" conference held at the University of Maine in January 1993, a panel explored the issue of privatization, of using private enterprise to provide public sector services. John Hanson raises concerns about possible drawbacks and consequences in the rush to privative, including self-interest, efficiency, accountability and decreased employment.